Genetics of Socio-Cultural Systems - I. N. Drogobytskii (Мир новой экономики, 2019)
The euphoria of the effectiveness of the methodology of system modelling in the study of nature and synthesis of artificial systems has prompted the scientific community to its large-scale use in the sciences, the subject of which is the human community: economics, sociology, political science, history, philosophy, etc. However, many years of work in this field have not yet led to significant success. It turned out that the systems in which the key role belongs to man — socio-cultural, are fundamentally different from natural and artificial systems, and the methods of their research are not always applicable to their analysis. We need a specific methodology for modelling socio-cultural systems, and therefore the theoretical justification of its applicability. In this article, the author provides an original classification of systemic formations, which allows to clearly divide the whole set of systems into non-intersecting subsets (classes) and to define the limits of the efficacy of the existing arsenal of system modelling. In order to expand it and extend it to the class of socio-cultural systems, the author justified the original approach to the description of system dynamics and proposed an appropriate modelling language. The author proved the analogy in the development of socio-cultural and living systems and substantiated the proposition of the expediency of initiating a new scientific stream in the study of human community activity — genetics of socio-cultural systems.